Parental Involvement In The Education Of Children With Special Needs (A Case Study At Elmafaza Inclusive School) ny - Kelik Wardiyono; Septian Teja Irawan; Budi Lenggono; Yessy Yanita Sari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Parental involvement in the educational process has a positive significance for educational outcomes, including in the educational process in inclusive schools. Understanding the forms of parental involvement in the inclusive school education process will help provide the best way for children with special needs in their educational success. The purpose of this study was to analyze the form of parental involvement in the education of children with special needs in inclusive schools. The research uses a qualitative approach. Data was collected by interview, documentation, and observation methods. The interactive qualitative analysis technique of the Miles and Huberman model which consists of data reduction, data presentation and conclusion drawing is used in the research. The results showed that there are various forms of parental involvement, including acting as models of behaviour, ethics, and independence (parental modelling), giving reinforcement when a willingness to learn appears in children (parental reinforcement), and giving encouragement/stimulant so that children's cognitive abilities develop (parental encouragement). Parental involvement can foster internal motivation and self-regulation strategies in children.